Synthesis And Characterization Of Fe-Doped Zinc Oxide Rods - Abd Aziz, Siti Nor Qurratu Aini (2014)
Chemical vapor deposition (cvd) technique is the most common vapor route technique uses by researchers to synthesize zno nanostructures. However, the current in-situ doping approaches using cvd do not give many flexibilities for the researchers to produce doped zno nanostructures. As the dopant solution is kept outside the furnace, the aerosol assisted - chemical vapor depostion (aa-cvd) is a potential in-situ doping technique because it offers many advantages such as flexibility of controlling the doping concentration, doping duration, type of dopant precursor and possibility of mass production of doped nanostructures. This project started by setting up a cvd system to synthesize undoped zno rods without using foreign catalyst. The study indicated that the optimum synthesis condition for synthesizing undoped zno rods was using 0.3 g zn powder, 30 min synthesis duration, and 5 cm distance of si substrates from zn powder at 650 °c. The average length, diameter, aspect ratio and areal density of undoped zno rods are 2.99 ±0.13 pm, 0.54 ± 0.05 pm, and 5.6 ± 0.3, 2.9 ± 0.9 rods/pm , respectively. Subsequently, ex-situ fe-doping was performed via spray pyrolysis on the pre-grown zno rods. The physical properties of fe-doped zno rods prepared by ex-situ doping would be used to compare with the fe-doped zno rods prepared by in-situ doping in the subsequent phase.